2021
DOI: 10.1111/cdev.13633
|View full text |Cite
|
Sign up to set email alerts
|

Princess Power: Longitudinal Associations Between Engagement With Princess Culture in Preschool and Gender Stereotypical Behavior, Body Esteem, and Hegemonic Masculinity in Early Adolescence

Abstract: Princess culture is criticized for contributing to gender stereotypes and poor body esteem, however, there is little longitudinal research examining these claims. This study examines associations between engagement with princess culture during early childhood and gender stereotypes, body esteem, and adherence to hegemonic masculinity in early adolescence. Participants included 307 children (51% female, M age = 4.83 years, 87% White) who completed questionnaires at two time points, 5 years apart. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
0
17
1
2
Order By: Relevance
“…Contrasting to the research of Botta (1999, 2000), Coyne et al (2021) observed higher body esteem among children who engaged with the Disney princess culture over a 5-year period. Princess culture engagement included the level of identification with princesses and interactions with princess media and toys.…”
Section: Literature Reviewcontrasting
confidence: 95%
See 4 more Smart Citations
“…Contrasting to the research of Botta (1999, 2000), Coyne et al (2021) observed higher body esteem among children who engaged with the Disney princess culture over a 5-year period. Princess culture engagement included the level of identification with princesses and interactions with princess media and toys.…”
Section: Literature Reviewcontrasting
confidence: 95%
“…Because media viewing influences attitudes and behaviors, comparison can generate either motivations to improve one’s behavior and/or perpetuate negative responses, such as dissatisfaction. Children, for example, compare themselves with characters presented in the media they consume and, as a result, develop either a positive or negative self-perception (Botta, 2000; Coyne et al, 2021; Thomsen, 2002). Botta (1999) found the amount of TV viewing and viewing TV dramas with predominately thin characters influenced high school girls’ desire for thinness, body dissatisfaction, bulimic behaviors, and their perpetuation of the thin ideal.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations